The Legality Of Passage Of Nuclear-powered Submarines: Are Malaysia And Indonesia In Catch-22? - Mohd Hazmi Mohd Rusli (Moscow State Institute of International Relations, 2024)
INTRODUCTION Southeast Asia is home to some of the most important sea lines of communication (MLS), which are not only important sea routes for merchant ships, but also for the warships of the superpowers. Although no accidents involving nuclear submarines have yet been recorded in this region, the fact remains that the number of such vessels passing through the Southeast Asia maritime link is predicted to increase in the coming years.